The impact of higher education on university student entreprenurial intention/ Noor Jannah Fatimah - Fatimah, Noor Jannah (2015)
There are many opportunities provided by government to the entrepreneurship program for people in our country. As the main character the youth are responsible to ensure that more entrepreneur will be created. The opportunity should be grabbed to increase the economy for the county. The development of business potential of the student during study will lead to increase of its competitiveness in the market. The opinions of experts on existing problems in the course of entrepreneurial from the point of view of their focus on development at students of enterprise qualities are analyzed. The results of applied research of entrepreneurial orientation of students prove the existence by students the positive elation to business and desire to develop enterprise potential during study. Also, in the paper the main directions of improvement of system of formation and development of enterprise potential of students are formulated.